2016
DOI: 10.5114/aoms.2016.58622
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of erythropoietin against oxidant injury following brain irradiation: an experimental study

Abstract: IntroductionRadiation therapy (RT) is a major treatment modality, and the central nervous system is a dose-limiting organ in clinical RT. This experimental study aims to present the evaluation of the neuroprotective effects of erythropoietin (EPO) against oxidant injury following brain irradiation in rats.Material and methodsForty Wistar rats were randomly assigned to four groups (n = 10 each). In group 1 the rats received no EPO and underwent sham RT. The rats in groups 2 and 3 received EPO. In group 2 rats u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…It is believed that EPO protects neurons through a combination of these mechanisms. [7,8] EPO modulates neuroinfl ammation through neurotrophic actions on astrocytes, microglia and neurons. [9] It can pass through the blood-brain barrier and acts on the central nervous system through inhibition of apoptosis in microvascular endothelial cells and activation of astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that EPO protects neurons through a combination of these mechanisms. [7,8] EPO modulates neuroinfl ammation through neurotrophic actions on astrocytes, microglia and neurons. [9] It can pass through the blood-brain barrier and acts on the central nervous system through inhibition of apoptosis in microvascular endothelial cells and activation of astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been demonstrated that infusion of β-amyloid in rats resulted in significant decrease of the antioxidant capacity [32,33]. Oxidative stress and related degeneration of cholinergic neurons is one of the most common sharing pathways involved in neurodegenerative disorders such as AD [34][35][36]. The brain is more susceptible to reactive oxygen species (ROS)-mediated injury because its cellular membranes are preferentially enriched in oxyradical-sensitive polyunsaturated fatty acids that are the substrates of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Ugurluer evaluated the effect of Epo against oxidant injury following brain radiotherapy in experimental model. He showed a pos-itive neuroprotective effect of Epo connected with decreasing free radical production and increasing expression of antioxidant enzymes [42].…”
Section: The Neuroprotective Effects Of Erythropoietinmentioning
confidence: 99%